Antioxidant Activity of Methanol Extract Leaves of Neem (Azadirachta indica) - Bahri, Syamsul; Wirdullutfi, Wirdullutfi; Hijriani, Baiq Isti (Jurnal Biologi Tropis, 2025)
Azadirachta indica Juss. (neem), a medicinal plant belonging to the Meliaceae. The leaves of this species contain bioactive compounds such as flavonoids, alkaloids, steroids, saponins, tannins, and azadirachtin. These compounds exhibit antimicrobial activity against Salmonella and Escherichia coli. This study aimed to determine the antioxidant activity of the neem leaves' methanol extract by using the DPPH method. The research method used phytochemical screening by separating chemical compounds from samples using 70% methanol solvent. The result showed that the antioxidant activity of the neem leaves' methanol extract is classified in the weak category with an IC50 score of 426.15 mg/mL. One of the main factors explaining the high IC50 values is the differences in the chemical structure and molecular shape of the secondary metabolites contained in the extracts. The antioxidant activity of flavonoids and phenolics is greatly influenced by the number and position of hydroxyl groups, the degree of conjugation, and the presence of sugar groups.